Prevalence and Diagnosis of Rifampicin-Resistant Mycobacterium Tuberculosis using the GeneXpert MTB/RIF Assay at a Tertiary Care Children's Hospital: Prevalence and Diagnosis of Rifampicin-Resistant Mycobacterium Tuberculosis - Jameel, Rabyya; Mehdi, Naima; Majeed, Nadia; Zafar, Aizza; Tahir, Anum; Aroob, Iqra (Pakistan Journal of Health Sciences, 2024)
Rifampicin is a primary anti-tuberculosis medication. Diagnosing multidrug-resistant tuberculosis (MDR-TB) remains a persistent challenge when examining both pulmonary and extra-pulmonary samples. Rapid detection of rifampicin resistance is essential for the timely treatment and prevention of the spread of tuberculosis. Recently, GeneXpert MTB/RIF assay has emerged as an advanced technique for the rapid diagnosis of Mycobacterium tuberculosis. Objectives: To assess the prevalence of rifampicin resistance in samples from pediatric patients in Pakistan, encompassing both pulmonary and extra-pulmonary cases using GeneXpert MTB/RIF assay. Methods: A cross-sectional study was conducted in the Children’s Hospital, Lahore for a duration of six months. Pulmonary and extra pulmonary samples of patients under age 16 were examined by GeneXpert MTB/RIF assay. Results: A total of 1320 samples were examined, and among them, 110 tested positive for M. tuberculosis (MTB) infection. Out of these 110 positive samples, 5 exhibited resistances to rifampicin, 18 showed indeterminate resistance, while rifampicin resistance was not detected in the remaining 87 samples. Additionally, 3 of the rifampicin-resistant samples displayed a very low load of MTB, and 2 samples exhibited a low MTB load. Conclusions: This study revealed 4.5% prevalence of MDR-TB in pediatric population. The study also showed that GeneXpert is a highly advanced technique for the diagnosis of rifampicin resistance in pulmonary and extra-pulmonary samples.